Nuclear Medicine Technology Review Questions for the Board Examinations - Mantel, Eleanor (Springer International Publishing, 2018)
This book prepares students and technologists for registry examinations in nuclear medicine technology by providing practice questions and answers with detailed explanations, as well as a mock registry exam. The questions are designed to test both the basic knowledge required of nuclear medicine technologists and the practical application of that knowledge. The topics covered closely follow the content specifications and the components of preparedness as published by the certification boards. This 5th edition includes expanded coverage of positron emission tomography, multimodality imaging, and other new procedures and practices in the field of nuclear medicine and molecular imaging.